Uji Efek Aplikasi Takaran Biochar dan Kompos Kirinyuh Tahun Ke Dua terhadap Pertumbuhan dan Hasil Selada Darat (Lactuca SativaL.) - Eduardus Yosef Neonbeni; Veronika Boe; Arnoldus Klau Berek (Savana Cendana, 2019)
Lactuca sativa L. is a horticultural vegetable commodity that has high prospects and commercial value. This study aims to examine the effects of biochar and second-year compost applications on soil physical properties, growth and yield of ground lettuce. The research was conducted in March-May 2018, at the experimental farm of the Faculty of Agriculture, University of Timor. The design used in the study was a 5 x 3 factorial completely randomized design which was repeated 3 times. The first factor is the biochar dose which consists of 5 levels, namely 0 t/ha, 2.5 t/ha, 5 t/ha, 7.5 t/ha and 10 t/ha. The second factor is the left compost, which consists of 3 levels, namely without compost left (0 t/ha), 5 t/ha, and 10 t/ha. The mixture of soil, biochar and leftover compost used the previous year, is dried, mashed, sifted and put back in the pot, watered and planted with Lactuca sativa L. seeds that have been sown 2 weeks earlier. Parameters observed in this study were soil temperature, moisture content, electrical conductivity, soil pH, soil volume weight, plant height, number of leaves, leaf area, fresh weight per plant, dry weight per plant, root length, fresh weight. root, root dry weight, root shoot ratio, harvest index. The results showed that biochar treatment at a rate of 2.5 t/ha yielded the heaviest fresh trubus 16.64g / plant, higher than the first year (0 t/ha), while the leftover compost at a rate of 10 t/ha produced fresh trubus weighing 15.11g. / plant higher than the first year yield (0 t/ha). These results indicate an aging effect of the application of rice husk biochar and leftover compost on the growth and yield of Lactuca sativa L.